The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages myself recently, at which certain members got heated because there were applicants seeking dentures. Some members of the Committee were expressing the opinion that they would not mind being claimants themselves for dentures. That is the sort of outlook you get in these Committees. The poor fellow seeking assistance gets a prescription from his doctor which he takes to the chemist. The only square meal the doctor can prescribe is one in the shape of an Oxo Cube. The scale of existence for himself and his family is decided by the Public Assistance Committee allowances and I can assure you no one can have a decent standard of health on such an allowance which barely allows a man to live. We need the organisation of the working class to realise that a basic requirement of any decent National Health Service must be a decent standard of feeding. The miserable allowance of the Public Assistance Committee and the Labour Exchange do not provide such a standard. ASSUMPTION B. Now we have the long promised White Paper on Assumption B. of the Beveridge Report coming along and what it is going to do is not going to be particularly helpful towards a National Health Service. We have our British Hospitals Association which has already announced its opposition to any scheme which affects the position of the Voluntary Hospitals. We have the British Medical Association who, for the best part, are opposed to the terms of the Beveridge proposals. Then we have the British Medical Council too. All are autocratic bodies and all are opposed to progress. There are the Royal College of Surgeons and the Royal College of Physicians too. They can bring a lot of pressure to bear on questions of this kind. It is under this system that Research is stifled to such an extent, that I doubt if more than £200,000 a year is spent on medical research at the present moment and I would say that at the least £12,000,000 a year is needed for adequate research. Some people appear to have the idea that all health workers are doctors and nurses. That is all wrong because there are many thousands of us who contribute towards the work of the specialists. There are domestic staffs, ambulance services, health visitors, midwives, first-aid workers and many others. When the T.U.C. made a stink about the rotten conditions of nursing staffs, we got the Athlone Committee set up and eventually the Rushcliffe Committee to enquire into these conditions. The Rushcliffe Committee issued a Report and since then we have had a number of further reports to interpret the first one. Now we are going to have another committee to enquire into the wages and conditions for various medical staffs in hospitals and institutions. One of the members of the committee is a professor, he is the chairman. One is an industrialist and another is a trade union official. I have wondered and others must have wondered too, just what qualifications they have for this particular job. Anyhow they have a job to do and I understand their Report will soon be issued. 23 15X/2/103/295